Batas Kewenangan Advokat dalam Membela Klien terkait dengan Delik Obstruction of Justice - Rizal Hamdani; Prasetijo Rijadi (Prosiding Seminar Nasional Ilmu Hukum, 2024)
The issue of accusations of obstructing or obstructing the legal process carried out by the Advocate in his capacity to defend the client is problematic. The aim of this study is to describe the right to immunity possessed by advocates in the aspect of law enforcement. As well as aiming to find out the criminal liability of Advocates for Obstruction of Justice carried out during the legal process. This writing uses the normative law research method, which is a method or method used in one of the legal research conducted by reviewing the literature and aimed at written regulations. This study show that the right to immunity applies as long as there is good faith that can be held accountable by the Advocate both outside and in the trial in order to protect the legal interests of his client. Meanwhile, in the criminal aspect against Advocates who are proven to have committed obstruction of justice and injured good faith by committing acts that are against the Law to obstruct the law enforcement process.